Mixed Grazing and Dietary Supplementation Improve the Response to Gastrointestinal Nematode Parasitism and Production Performances of Goats - Bambou, Jean-Christophe; Ceï, Willy; Arquet, Rémy; Calif, Valériuse; Bocage, Bruno; Mandonnet, Nathalie; Alexandre, Gisèle (Frontiers in Veterinary Science, 2021)
Small ruminants are very affected by gastrointestinal nematode (GIN) parasitism worldwide. The improvement of the host protective response and the reduction of the probability of contact between hosts and parasites appear as very promising strategies. The objective of this study was to evaluate the effect of a combination of two components of these two strategies on natural GIN infection and production performances of Creole goat kids: dietary supplementation and a rotational mixed grazing system. One hundred and twenty weaned Creole kids and 6 Creole heifers were divided into 4 experimental batches: Splus (supplemented) vs. Szero (non-supplemented) × Mixed grazing (kids associated with heifers) vs. Control (kids alone), grazing plots of forage grasses were balanced for live weight (LW) in both species. The feed intake, blood and parasitological parameters and production performances between 3 and 11 months of age were monitored. The faecal egg count (FEC) was significantly lower and the packed cell volume (PCV) significantly higher in the Mixed grazing groups. No effect of supplementation was observed for FEC. In contrast, PCV, body condition score and live weight were significantly higher in supplemented animals whatever the groups. Mixed grazing system and supplementation had significant effects on the slaughter parameters (P < 0.05) but there was no significant interaction. Our results suggested that the advantage driven either by mixed grazing or dietary supplementation on kids performances would be equivalent and the combination of both would improve the animal performances.